Expert system for adopting wireless identification technologies (WIT) in healthcare; fundamentals and applications - Barbosa Ávila, J. G.; Dieck-Assad, Graciano (Revista Mexicana de Ingenieria Biomedica, 2011)
The wireless identification technologies or WIT are all the technologiesand applications for contact-less automatic identification. The term WIT implies that no visual or mechanical contact is necessary to transfer information about the identification of a device, product or process. WIT is a fertile and relevant field of study in healthcare. Among the new generation of innovative technologies, WIT provides enabling devices that improve the machine perception and integration. However, for non-experts particularly in the healthcare areas, the decision to adopt wireless identification technologies is a relatively complex process due to the wide variety of available options and the limited time of certified experts. This article demonstrates that it is possible to bridge the gap between the functional and technical requirements of WIT in healthcare institutions. This is achieved by developing an expert system to provide unbiased information about the most suitable technology for specific applications in healthcare. This article proposes an expert system to provide the initial fundamental platform to facilitate and stimulate the adoption of WIT in the healthcare industry. The system is tested in a private hospital to make appropriate decisions in the adoption and use of WIT in the hospital environments. Results of tests performed with the expert system show dominance of the following technologies for healthcare facilities: UHF RFID active working both, at 915 MH and 433 MH, UHF RFID passive working at 915 MH, Ultrasound working from 20 to 60 MH, and uW Active RFID working at 2.45 GHz.